(untitled) (Ustozlar uchun, 2025)
The rapid globalization of business operations has significantly expanded international career opportunities for managers. Modern companies increasingly seek professionals capable of leading multicultural teams, adapting to global market changes, and utilizing digital technologies for cross-border operations. This article analyzes the main trends shaping global managerial careers, the competencies required for international mobility, and the challenges faced by managers entering the global workforce. Practical recommendations are provided for developing global leadership skills and improving competitiveness in the international labor market.